Link between past threatening experience and future neophobic behaviour depends on physiological stress responsiveness. (September 2020) - Bebus, Sara E.; Jones, Blake Carlton; Schoech, Stephan J.
Abstract : Past threatening experiences, such as exposure to a predator or a capture event, can influence an animal's future behaviour, with profound consequences on its survival and ultimate fitness. We hypothesize that an animal's physiological stress response phenotype modulates the influence of past experiences on future behaviour in the Florida scrub-jay, Aphelocoma coerulescens, a species that exhibits individual physiological stress response phenotypes that are repeatable across a life span. We subjected young, trap-capture-naïve Florida scrub-jays to a standardized capture and restraint protocol to quantify stress-induced levels of circulating glucocorticoids. Twenty-four hours later, we assessed their response to a novel object and compared this measure of neophobia to age-matched individuals that had never been captured in a trap. We predicted that individuals trapped prior to novel object trials would be more neophobic than noncaptured controls. Furthermore, we predicted that scrub-jays with high glucocorticoid responses would be the most neophobic. Indeed, previously captured individuals had longer latencies to approach and enter a novel ring compared to controls. Past trap experience interacted with a bird's physiological phenotype to influence their neophobic behaviour. Contrary to our predictions, trapped birds with a low glucocorticoid response phenotype were more neophobic compared to low response controls, whereas trapped individuals with a high response phenotype where less neophobic compared to high response controls. Our results demonstrate that experience can affect individuals differently depending on their physiological phenotype. This novel finding highlights the need to consider how differential responses to invasive and captive protocols may confound results of behavioural studies involving free-living subjects. Highlights: Threatening experiences can influence future behaviour. We tested whether corticosterone (CORT) responsiveness influenced this relationship. After capture, low CORT response birds were more neophobic than low CORT controls. After capture, high CORT response birds were less neophobic than high CORT controls. Capture experience may differentially affect neophobia response.